Observational insights into chlorophyll distributions of subtropical South Indian Ocean eddies. Issue 7 (9th April 2017) - Dufois, François; Hardman‐Mountford, Nick J.; Fernandes, Michelle; Wojtasiewicz, Bozena; Shenoy, Damodar; Slawinski, Dirk; Gauns, Mangesh; Greenwood, Jim; Toresen, Reidar
Abstract: The South Indian Ocean subtropical gyre has been described as a unique environment where anticyclonic ocean eddies highlight enhanced surface chlorophyll in winter. The processes responsible for this chlorophyll increase in anticyclones have remained elusive, primarily because previous studies investigating this unusual behavior were mostly based on satellite data, which only views the ocean surface. Here we present in situ data from an oceanographic voyage focusing on the mesoscale variability of biogeochemical variables across the subtropical gyre. During this voyage an autonomous biogeochemical profiling float transected an anticyclonic eddy, recording its physical and biological state over a period of 6 weeks. We show that several processes might be responsible for the eddy/chlorophyll relationship, including horizontal advection of productive waters and deeper convective mixing in anticyclonic eddies. While a deep chlorophyll maximum is present in the subtropical Indian Ocean outside anticyclonic eddies, mixing reaches deeper in anticyclonic eddy cores, resulting in increased surface chlorophyll due to the stirring of the deep chlorophyll maximum and possibly resulting in new production from nitrate injection below the deep chlorophyll maximum. Key Points: Bio‐Argo float data elucidate biogeochemical dynamics in a productive anticyclonic ocean eddy in the South Indian Ocean subtropical gyre Stirring of the deep chlorophyll maximum by anticyclonic eddy‐induced mixing leads to enhanced surface chlorophyll Advection of productive waters can also enhance surface chlorophyll in anticyclonic eddies